Food for thought: probiotic modulation of microglial activity in Parkinson's disease - Kroker Kimber, Isabella; Tremblay, Marie-Ève (Frontiers in Molecular Neuroscience, 2025)
The gut-brain axis is emerging as a key player in Parkinson's disease (PD), with growing attention on how the gut microbiome (GM) shapes microglial activity, a central driver of neuroinflammation and dopaminergic loss. GM dysbiosis, characterized by reduced beneficial microbes and increased proinflammatory taxa, can compromise intestinal barrier integrity, activate systemic immunity, and prime microglia toward a proinflammatory state, potentially facilitating α-synuclein misfolding and propagation from gut to brain. Preclinical studies reveal that probiotics can rebalance microbial communities, enhance short-chain fatty acid production, reinforce intestinal barrier integrity, and modulate immune responses, effects collectively linked to reduced microglial reactivity, lower α-synuclein aggregation, and improved motor outcomes in PD models. Human trials of probiotic supplementation in PD, primarily investigating gastrointestinal and non-motor symptoms, suggest potential benefits for systemic inflammation and neuroimmune signaling, though direct evidence of central microglial modulation is limited. By synthesizing animal and clinical data, this review underscores both the therapeutic promise of probiotics and identifies current gaps in leveraging microbiota-based interventions as non-invasive, disease-modifying strategies for PD.